Five-year retrospective analysis of Bakri balloon tamponade for obstetric haemorrhage and patient survey at a single tertiary centre - Tithi Kulkarni; Ruth McCuaig; Gargeswari Sunanda (Journal of Obstetrics and Gynaecology)
Background Intrauterine balloon tamponade (IUBT), specifically the usage of Bakri balloon tamponade (BBT), is an effective conservative management technique for postpartum haemorrhage (PPH). The primary objective was to evaluate local guidelines and contribute to evidence regarding ideal duration for BBT. The secondary objectives were to consider impacts on maternal-foetal wellbeing, and optimise healthcare efficiency by reducing length of ICU admissions.Methods This five-year retrospective case series analysed 132 cases of obstetric ICU admissions requiring Bakri balloon insertion for PPH within our centre. Additionally, a prospective patient experience survey was conducted over six-month period, involving 22 obstetric patients who required unplanned ICU admissions.Results Bakri balloon insertion was successful in 95%, whilst 5% experienced failure, necessitating further interventions (uterine artery embolisation) or return to theatre (hysterectomy). The success group demonstrated significant reductions in median blood loss (1.8 L vs. 2.5 L, p = 0.016) and difference in median duration of BBT (18.3 vs. 3.92 hours, p = 0.001). The prospective patient survey revealed a high level of satisfaction of care. Approximately 50% breastfed prior to discharge, on average commencing 23.4 hours post-delivery. This study demonstrates a high success rate of BBT, with failures typically occurring within median duration 3.9 hours.Conclusions Considering the separation of mother from baby during the Bakri balloon’s presence in ICU, we propose timely removal at around six hours, as failures are unlikely post this timeframe, or nursing these women in a neonatal care setting to facilitate earlier mother-baby bonding.